(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2017)
Subacute sclerosing panencephalitis (SSPE) is a chronic encephalitis of childhood and young adolescence due to persistent measles virus infection of the central nervous system (CNS). In majority of cases, onset occurs between 5-10 years of age. SSPE generally occurs 5-10 years after measles virus infection1. The diagnosis of SSPE is based on characteristic clinical and electroencephalogram (EEG) findings, increase measles antibody titer in cerebrospinal fluid (CSF) and serum. As onset of SSPE in adults is rare and may have atypical feature it requires high index of suspicion for early and accurate diagnosis. Herein, we report a case of SSPE in a male of 26 years with recurrent episodes of myoclonic jerks. Journal of National Institute of Neurosciences Bangladesh, 2016;2(1): 40-42